Integrated GC–MS- and LC–MS-Based Untargeted Metabolomics Studies of the Effect of Vitamin D3 on Pearl Production Traits in Pearl Oyster Pinctada fucata martensii - Yang, Chuangye; Zeng, Yetao; Liao, Yongshan; Deng, Yuewen; Du, Xiaodong; Wang, Qingheng (Frontiers in Molecular Biosciences, 2021)
Pearl oyster Pinctada fucata martensii is widely recognized for biomineralization and has been cultured for high-quality marine pearl production. To ascertain how dietary vitamin D3 (VD3) levels affect the features of pearl production by P. f. martensii and discover the mechanisms regulating this occurrence, five experimental diets with variable levels of VD3 were used with inclusion levels of (0, 500, 1000, 3000, and 10000 IU/kg). The distinct inclusion levels were distributed into five experimental groups (EG1, EG2, EG3, EG4, and EG5). All the experimental groups were reared indoors except the control group (CG) reared at the sea. Pearl oysters, one year and a half old, were used in the grafting operation to culture pearls. During the growing period that lasted 137 days, EG3 had the highest survival rate, retention rate, and high-quality pearl rate. A similar trend was found for EG3 and CG with significantly higher pearl thickness and nacre deposition rates than other groups, but no significant differences were observed between them. A metabolomics profiling using GC–MS and LC–MS of pearl oysters fed with low quantities of dietary VD3 and optimal levels of dietary VD3 revealed 135 statistically differential metabolites (SDMs) (VIP > 1 and P < 0.05). Pathway analysis indicated that SDMs were involved in 32 pathways, such as phenylalanine metabolism, histidine metabolism, glycerophospholipid metabolism, alanine aspartate and glutamate metabolism, arginine and proline metabolism, glycerolipid metabolism, amino sugar and nucleotide sugar metabolism, and tyrosine metabolism. These results provide a theoretical foundation for understanding the impacts of VD3 on pearl production traits in pearl oyster and reinforce forthcoming prospects and application of VD3 in pearl oyster in aquaculture rearing conditions.